Polyhydroxyalkanoate Production from Municipal Waste Material (Chemical Engineering Research Bulletin, 2026)
The utilization of waste material as a resource to produce polyhydroxyalkanoate (PHA) through anaerobic digestion has been identified as a cost-effective approach to the production of bioplastic. This approach involves the conversion of waste material as cost effective substate for PHA production through anaerobic digestion, which is a process that occurs in the absence of oxygen. The resulting bioplastic can be used as a sustainable alternative to traditional petroleum-based plastics. The present research investigates the feasibility of utilizing volatile fatty acids (VFAs) containing leachate, a significant component generated from municipal solid waste through anaerobic digestion, as a feedstock to produce polyhydroxyalkanoate (PHA). However, leachate contains variable concentrations of carbon and nitrogen. To evaluate the effect of enrichment history on PHA producer and production the various carbon and nitrogen levels were utilized during the accumulation phase.In this study, the possibility of mixed culture polyhydroxy alkynoate (PHA) production from waste material was assessed by studying the effects of various carbon and nitrogen levels. For this assessment, Polyhydroxyalkanoate (PHA) producing bacteria was cultured from a mixed microbial culture (MMC) using feast famine (FF) process and acetate and ammonium sulphate as nutrient source. The maximum PHA production of the enriched cultures under nutrient starvation (41%) was evaluated in batch assays. Excess substrate feeding during nutrient excess condition maximizes the PHA production. The influence of the C/N ratio on PHA accumulation capability was evaluated by supplementing the leachates. Leachate can be a promising and sustainable source for PHA production, with a C/N ratio of 3:1 resulting in a yield of 0.1g-PHA/g substrate.Chemical Engineering Research Bulletin: 24 (Issue 1): 13-19